2014
DOI: 10.1590/abd1806-4841.20142869
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of methotrexate in alopecia areata

Abstract: BACKGROUNDAlopecia areata is a chronic disorder of the hair follicles and nails, of unknown etiology, with clear autoimmune components and genetic factors. Several therapeutic options have been suggested; however, no treatment is able to modify the disease course. Methotrexate is an immunosuppressant used in various dermatoses and recently introduced as a therapeutic option for alopecia areata.OBJECTIVESTo evaluate the efficacy and safety of methotrexate in alopecia areata.METHODSIn a retrospective, non-contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 22 publications
(36 reference statements)
1
40
1
4
Order By: Relevance
“…A previous study found an 80% relapse rate and another recent study reported 33% relapse rate in patients with more than 50% regrowth1319 In our study, 9 patients (31.0%) with >75% hair regrowth experienced recurrent of disease. The difference between recurrence rates may be due to differences in the severity of disease, disease duration, cumulative MTX dose and concomitant medication.…”
Section: Discussionsupporting
confidence: 56%
“…A previous study found an 80% relapse rate and another recent study reported 33% relapse rate in patients with more than 50% regrowth1319 In our study, 9 patients (31.0%) with >75% hair regrowth experienced recurrent of disease. The difference between recurrence rates may be due to differences in the severity of disease, disease duration, cumulative MTX dose and concomitant medication.…”
Section: Discussionsupporting
confidence: 56%
“…This finding is similar to that in the series by Chartaux and Joly [17], who reported a relapse rate of 80%. In another series in Brazil of patients who received MTX, the relapse rate was 33% for patients with more than 50% of initial regrowth [20]. However, we found no clinical factor associated with later relapse.…”
Section: Discussioncontrasting
confidence: 51%
“…Hammerschmidt and Mulinari-Brenner [20] recently found that for patients receiving MTX, multifocal AA and disease duration <5 years were associated with a better response to treatment. In our study, treatment response was improved, although not significantly, for patients with reduced disease duration (3.5 and 7.8 years for responders and nonresponders, respectively) and multifocal AA (78% of responders).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concordant with this hypothesis, a considerable proportion of AA patients have one or more accompanying autoimmune diseases . In this context, various kinds of immunosuppressive agents such as dinitrochlorobenzene, squaric acid dibutylester (SADBE), diphenylcyclopropenone (DPCP) and methotrexate (MTX) have thus far proven their effectiveness and efficacy for AA in many studies …”
Section: Discussionmentioning
confidence: 99%